Impact Of Equestrian Tourism On The Environment - Ioan Petroman (Scientific Papers Animal Science and Biotechnologies, 2015)
Considereda sub-sector of horse raisin units, equestrian tourism is a form of moderntourism very popular among the young people as both an entertainingrecreational and adventure activity and a form of animal therapy in thetreatment and rehabilitation of autistic children; it is also a sub-type ofrural tourism, adventure tourism, or ecological tourism. Equestrian tourismpracticed without management strategies can have both positive and negativeeffects on the environment: it can affect roads by soil compaction, vegetationby the introduction of invasive plant species, and tourists by the noise andsmell. In order to reduce the negative effects on the environment, we need todevelop management strategies for the routes and visitors as well as for theareas where equestrian tourism is practiced; we also need to developenvironmental-friendly tourism products depending on the degree of difficulty,supplying accommodation at the horse farm and horse riding lessons,conferences, chart rides in the nature, and horseback holidays.